2016
DOI: 10.1017/s0305000915000860
|View full text |Cite
|
Sign up to set email alerts
|

Connective processing by bilingual children and monolinguals with specific language impairment: distinct profiles

Abstract: Production studies show that both Russian-speaking children with specific language impairment (SLI) and bilingual children for whom Russian is a non-dominant language have difficulty distinguishing between the near-synonymous connectives i 'and' and a 'and/but'. I is a preferred connective when reference is maintained, whereas a is normally used for reference shift. We report an eye-tracking experiment comparing connective processing by Russian-speaking monolinguals with typical language development (TLD) with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 37 publications
0
10
1
1
Order By: Relevance
“…text micro- and macro-structure; Cain et al, 2005; Cain & Nash, 2011; Carretti, Motta, & Re, 2016; Crosson & Lesaux, 2013; Levorato & Zammuner, 1985; Peterson, 1986; Tribushinina, Dubinkina, & Sanders, 2015; Vion & Colas, 2005). For instance, the recent work of Tribushinina and colleagues (2015; see also Mak et al, 2017) on Russian 7-year-olds showed that the correct use of two quasi-synonymous connectives in a narrative task required both the understanding of semantic relations between events at the text level and the integration of semantic and syntactic information of connectives at the sentence level.…”
mentioning
confidence: 99%
“…text micro- and macro-structure; Cain et al, 2005; Cain & Nash, 2011; Carretti, Motta, & Re, 2016; Crosson & Lesaux, 2013; Levorato & Zammuner, 1985; Peterson, 1986; Tribushinina, Dubinkina, & Sanders, 2015; Vion & Colas, 2005). For instance, the recent work of Tribushinina and colleagues (2015; see also Mak et al, 2017) on Russian 7-year-olds showed that the correct use of two quasi-synonymous connectives in a narrative task required both the understanding of semantic relations between events at the text level and the integration of semantic and syntactic information of connectives at the sentence level.…”
mentioning
confidence: 99%
“…In narrative elicitation tasks, Tribushinina et al (2017a) show that 8-year old children made an error in 40% of the cases where they used i for reference shift. At the same time Mak et al (2017) show that 5-year children at the same complementary school performed similarly to a monolingual control group in the VWP-task. These results can be explained in terms of a higher processing load in the narrative elicitation task.…”
Section: Discussionmentioning
confidence: 88%
“…We used the materials from earlier experiments (Mak et al, 2013, 2017). These consisted of four types of items.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…В связи с этим русский язык представлен в учебных программах во всех уровнях образования и во многих странах мира [8]. Его значение явно возрастает в странах, где он ранее был обязательным предметом, как например, в бывших республиках СССР [7,4] В эмпирической части исследования было установлено, что студенты имеют идентичные оценки о зависимости эффективности учебно-воспитательного процесса от творчества преподавателей при обучении студентов русскому языку. Было установлено, что на оценку студентов не оказывает влияние год/курс учебы и их общая успеваемость.…”
unclassified